Choosing T-cell sources determines CAR-T cell activity in neuroblastoma - García-García, Lorena; G. Sánchez, Elena; Ivanova, Mariya; Pastora, Keren; Alcántara-Sánchez, Cristina; García-Martínez, Jorge; Martín-Antonio, Beatriz; Ramírez, Manuel; González-Murillo, África (Frontiers in Immunology, 2024)
Introduction: The clinical success of chimeric antigen receptor-modified T cells (CAR-T cells) for hematological malignancies has not been reproduced for solid tumors, partly due to the lack of cancer-type specific antigens. In this work, we used a novel combinatorial approach consisting of a versatile anti-FITC CAR-T effector cells plus an FITC-conjugated NBneuroblastoma (NB)-targeting linker, an FITC-conjugated monoclonal antibody (Dinutuximab) that recognizes GD2. Methods: We compared cord blood (CB), and CD45RA-enriched peripheral blood leukapheresis product (45RA) as allogeneic sources of T cells, using peripheral blood (PB) as a control to choose the best condition for anti-FITC CAR-T production. Cells were manufactured under two cytokine conditions (IL-2 versus IL-7+IL-15+IL-21) with or without CD3/CD28 stimulation. Immune phenotype, vector copy number, and genomic integrity of the final products were determined for cell characterization and quality control assessment. Functionality and antitumor capacity of CB/45RA- derived anti-FITC CAR-T cells were analyzed in co-culture with different anti-GD2-FITC labeled NB cell lines.Results: The IL-7+IL-15+IL-21 cocktail, in addition to co-stimulation signals, resulted in a favorable cell proliferation rate and maintained less differentiated immune phenotypes in both CB and 45RA T cells. Therefore, it was used for CAR-T cell manufacturing and further characterization. CB and CD45RA-derived anti-FITC CAR-T cells cultured with IL-7+IL-15+IL-21 retained a predominantly naïve phenotype compared with controls. In the presence of the NB-FITC targeting, CD4+ CBderived anti-FITC CAR-T cells showed the highest values of co-stimulatory receptors OX40 and 4-1BB, and CD8+ CAR-T cells exhibited high levels of PD-1 and 4-1BB and low levels of TIM3 and OX40, compared with CAR-T cells form the other sources studied. CB-derived anti-FITC CAR-T cells released the highest amounts of cytokines (IFN-γ and TNF-α) into co-culture supernatants. The viability of NB target cells decreased to 30% when co-cultured with CB-derived CAR-T cells during 48h.Conclusion: CB and 45RA-derived T cells may be used as allogeneic sources of T cells to produce CAR-T cells. Moreover, ex vivo culture with IL-7+IL-15+IL-21 could favor CAR-T products with a longer persistence in the host. Our strategy may complement the current use of Dinutuximab in treating NB through its combination with a targeted CAR-T cell approach.